The Collaboration of Human Resource Management and Line Management–An International Comparison - Szierbowski-Seibel, Klaas; Wach, Bernhard; Kabst, Rüdiger (Organization Management Journal)
The extant research advocates for the strategic integration of human resource management (HRM) in managerial decision making to foster firm performance. However, the empirical evidence of a stronger strategic integration of HRM is still limited, especially in terms of strategic guidelines such as a human resource (HR) strategy and international comparative matters. Drawing on responses from 588 German and US-based organizations and related to the new institutionalism theory, this study examines whether a HRM partnership (i.e., sharing responsibilities between HRM and line management) that represents a particular form of strategic integration of HRM is beneficial for organizations. In particular, we find international differences as a more pronounced HRM partnership increases employee turnover in the USA, whereas no significant changes are encountered in Germany. We further demonstrate that organizations located in the USA are more likely to have a formal HR strategy compared to those in Germany. However, this study can neither provide support for the direct effect of a HRM partnership on employee turnover nor of a moderation of this relationship through the HR strategy.